2009
DOI: 10.1029/2008jb005806
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic detection and finite element modeling of a slow slip event in the Costa Rica prism toe

Abstract: [1] We investigate transient fluid flux through the seafloor recorded near the Costa Rica trench during the 2000 Costa Rica Seismogenic Zone Experiment using a 2-D fully coupled poroelastic finite element model. We demonstrate that the observed hydrologic anomalies are consistent with a model of propagating slow slip at the subduction interface between the frontal prism and downgoing plate. There are two sources of volumetric strain that drive fluid flux at the seafloor in response to fault slip at depth: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…We suggest that this event may instead be located within the updip transition from seismic to aseismic behavior (Figure 10). The occurrence of episodic slow slip updip of the seismogenic zone has been suggested in Costa Rica based on evidence for hydraulic transients correlated with seismic tremor and slow slip [ Brown et al , 2005; LaBonte et al , 2009; Davis et al , 2011]. Outerbridge et al [2010]also suggest SSE slip updip of the seismogenic zone from shore‐based cGPS data, although the cGPS network in their study is comparatively sparse, and we contend that Outerbridge et al 's [2010] models for SSE slip updip of the seismogenic zone are not well constrained.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this event may instead be located within the updip transition from seismic to aseismic behavior (Figure 10). The occurrence of episodic slow slip updip of the seismogenic zone has been suggested in Costa Rica based on evidence for hydraulic transients correlated with seismic tremor and slow slip [ Brown et al , 2005; LaBonte et al , 2009; Davis et al , 2011]. Outerbridge et al [2010]also suggest SSE slip updip of the seismogenic zone from shore‐based cGPS data, although the cGPS network in their study is comparatively sparse, and we contend that Outerbridge et al 's [2010] models for SSE slip updip of the seismogenic zone are not well constrained.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon was observed on only three out of a total of 14 OBS instruments near the base of the continental margin. LaBonte et al [2009] used a 2‐D fully coupled poroelastic finite‐element model to show that the patterns of fluid flow could be matched by a dislocation on the plate interface at a depth of less than 4 km, propagating bilaterally at an average rate of ∼0.5 km d −1 and lasting 20 d or more. In 2003 pressure gauges in ODP (Ocean Drilling Program) boreholes approximately 60 km offshore of the Nicoya Peninsula recorded two transient events [ Davis and Villinger , 2006], also interpreted as evidence for a slow‐slip event.…”
Section: Discussionmentioning
confidence: 99%
“…Since the occurrence of the 2007 event, an additional coastal station (SAJU) has been installed, increasing offshore resolution in case of similar future events. The occurrence of a possible shallow slip event in 2000 [ Brown et al , 2005; LaBonte et al , 2009] and pressure transients observed in ODP boreholes offshore the Nicoya Peninsula in 2003 [ Davis and Villinger , 2006] and May 2007 [M. Hessemann, personal communication, 2009] suggests that the shallow slip patch in our low‐misfit model may be real, and we make that assumption in the following discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Six slow‐slip episodes were observed near Nicoya with an average recurrence interval of 21 ± 6 months [ Jiang et al , 2012]. The first episode, in early 2000, including three pulses of transient slow‐slip propagating at the shallow subduction interface, was suggested by correlated flow rate transients detected across three flowmeters at the frontal prism of the forearc [ Brown et al , 2005; LaBonte et al , 2009]. The transient signal was also accompanied with tremor‐like noise recorded on collocated ocean bottom seismometers [ Brown et al , 2005].…”
Section: Gps Data and Analysismentioning
confidence: 99%